Characterization of Microbial Communities and Antimicrobial Resistance Genes in Urban Wastewater in Three Cities in Vietnam - Thi My Hanh Vu; Futoshi Kurisu; Futoshi Hasebe; Masato Suzuki; Ikuro Kasuga (Journal of Water and Environment Technology)

(untitled)
The inappropriate usage of antibiotics is accelerating the prevalence of antimicrobial resistant bacteria (ARB) and antimicrobial resistance genes (ARGs) in Vietnam. Wastewater surveillance is a promising approach to monitor ARB and ARGs. In this study, ARB and ARGs were evaluated in domestic wastewater samples collected from three major cities (Hanoi, Hai Phong, and Bac Ninh) in northern Vietnam in November 2022. The ratios of cefotaxime-resistant Escherichia coli to total E. coli in domestic wastewater were relatively high (8.4% E5.7%). Quantitative PCR demonstrated that the relative abundance of the class 1 integron integrase gene to prokaryotic 16S rRNA genes ranged from 6.8 ÁE10∁E to 1.3 ÁE10∁E. In original wastewater samples, Arcobacter and Aeromonadaceae were dominant. Enterobacteriaceae, Enterococcaceae, and Acinetobacter became dominant after broth enrichment with meropenem, highlighting the prevalence of potential carbapenem-resistant bacteria in urban areas in Vietnam. PCR screening revealed that the enriched cultures had clinically important carbapenemase genes, such as blaNDM and blaKPC. A metagenomic analysis with hybrid capture enrichment revealed that the ARG compositions of influent samples in different cities were similar (i.e., similar ARGs were prevalent in urban areas). This study demonstrated the value of wastewater surveillance for evaluating characteristics of ARB and ARGs in urban areas in Vietnam.